Updated Measurements in Vineyards Improves Accuracy of Soil Erosion Rates. (1st January 2018) - Rodrigo‐Comino, Jesús; Davis, Jason; Keesstra, Saskia D.; Cerdà, Artemi
Abstract : Core Ideas: Stock unearthing method assumes that soil surface is planar between vines. Improved stock unearthing method enhances the survey due to extra measurements. Indispensable to consider the timing of the measures in relation to tillage events. Stock unearthing method underestimates soil erosion rates by –14.2% in 1‐d plowed vineyards. Stock unearthing method underestimates erosion rates by –37.8% in 86‐d plowed vineyards. Vineyards have proven to be one of the most degraded agricultural ecosystems due to very high erosion rates, which are typically measured at fine temporal and spatial scales. Long‐term soil erosion measures are rare, but this information may be indispensable for a proper understanding of the vineyard soil system, landscape evolution, and crop production. The stock unearthing method (SUM) is a common topographical measurement technique developed to assess long‐term erosion rates. The reliance of the SUM has been questioned and should be replaced by an improved measurement technique. In this paper, we demonstrate the added value (improved accurate, low cost, and faster than photogrammetrically methods) of the improved stock unearthing method (ISUM). It was shown that large errors may have been made in previous assessments of soil erosion on vineyards, as the old method did not make measurements in the inter‐row area or consider the timing of the erosion assessment in relation to tillage events. We found that this caused the SUM to severely underestimate soil erosion rates by –14.2 and –37.8% in 1‐ and 86‐d tillage vineyards in one location, respectively. Furthermore, the increased measurement resolution attained from the ISUM allowed for the detailed assessment of micro‐topographical change. Soil loss maps were able to detect the locational changes in soil depletion and accumulation, as well as continuous soil movement features in the inter‐row areas. Ultimately, this leads to a more accurate estimate of the actual soil erosion rates in vineyards.